Surface diffusion induced by low-energy bombardment with He ions: an exchange mechanism - Dudka, O.V.; Mazilov, A.A.; Gordienko, J.A. (Вопросы атомной науки и техники, 2017)
The radiation-induced surface diffusion of molybdenum adatoms was studied using molecular dynamics simulations based on a many-body tight-binding potential interpolated to the short-range repulsive screened Coulombic interactions. It was shown that the He ion impact is accompanied by an extensive surface mobility of Mo atoms. The long radiation-induced atomic jumps, spanning more than a nearest-neighbor distance, were revealed on the {110} terrace. The radiation induced exchange of Mo atoms colliding with Mo {110} surface was found in our mathematical simulations: there were observed exchange processes in which the radiation excited atom entered the surface and another surface atom emerged nearby. These results of MD simulations appear to be the first observation of exchange events in radiation-induced surface diffusion.